Nilai Pendidikan dalam Antologi Geguritan Piweling Karya Devika Herfianingtyas - Hikmatun Nazilah Muhamad; Khundaru Saddhono; Djoko Sulaksono (Universitas Sebelas Maret, 2023)
The purpose of this study is to describe and explain the educational value contained in the piweling geguritan anthology by Devika Herfianingtyas. This research is a qualitative descriptive research with a content analysis approach. The data in this study is in the form of words, phrases, or sentences in the piweling geguritan anthology by Devika Herfianingtyas. The data sources are in the form of documents, namely piweling anthology books, reference books, and relevant journals. The sampling technique in this study uses purposive sampling which is carried out selectively by selecting words, phrases, or sentences in the Piweling geguritan anthology that can represent the answer to the problem formulation that has been made. The data collection technique in this study was carried out by analyzing the educational value in the piweling geguritan anthology by Devika Herfianingtyas. The data analysis technique used in this study is an interactive analysis consisting of data collection, data reduction, data presentation, and conclusion drawing. Based on the results of the analysis, the educational values found in Devika Herfianingtyas' anthology of Piweling geguritan are religious values, moral values, social values, and cultural values.